Theoretical concepts and measurement prospects for BSM trilinear couplings: a case study for scalar top quarks - Henning Bahl; Johannes Braathen; Georg Weiglein (European Physical Journal C: Particles and Fields, 2023)
Abstract After the possible discovery of new heavy particles at the LHC, it will be crucial to determine the properties and the underlying physics of the new states. In this work, we focus on scalar trilinear couplings, employing as an example the case of the trilinear coupling of scalar partners of the top quark to the Higgs boson. We discuss possible strategies for experimentally determining the scalar top (stop) trilinear coupling parameter, which controls the stop–stop–Higgs interaction, and we demonstrate the impact of different renormalisation prescriptions for this parameter. We find that the best prospects for determining the stop trilinear coupling arise from its quantum effects entering the model prediction for the mass of the SM-like Higgs boson in comparison to the measured value. We point out that the prediction for the Higgs-boson mass has a high sensitivity to the stop trilinear coupling even for heavy masses of the non-standard particles. Regarding the renormalisation of the stop trilinear coupling we identify a renormalisation scheme that is preferred in view of the present level of accuracy and we clarify the source of potentially large logarithms that cannot be resummed with standard renormalisation group methods.